PENGARUH MASA KERJA OPERATOR DI PT INDEXIM UTAMA KALIMANTAN TENGAH TERHADAP PRODUKTIVITAS PENEBANGAN - Kurdiansyah Kurdiansyah (Jurnal Hutan Tropis, 2019)
The purpose of this study was to determine the work productivity of loggers operators in PT. Indexim Utama Kalimantan Tengah. The object observed in this study is the chainsaw operator with a working time of 1, 6 and 10 years. Analysis of the data used was a Randomized Block Design (RBD) with 3 replications to determine the effect of treatment, namely the operator's service life on logging productivity. The results showed operator A, the average time taken to cut trees was 24 minutes 10 seconds with an average volume of 30.10 m3 per hour. In operator B the average time spent cutting trees is 22 minutes 33 seconds with an average volume of 43.63 m3 per hour. Whereas in operator C the average time spent cutting trees is 44 minutes 16 seconds with an average volume of 19.29 m3 per hour.  The results of analysis of variance showed that working time did not significantly affect logging productivity